A novel R^2-FLC dynamic buffer size tuner to support time-critical applications over the Internet by improving logical channel fault tolerance to shorten roundtrip time - Lin, W.; Wong, A.; Dillon, Tharam S. (IEEE, 2005)
This paper has two original and important proposals: a) the self-similarity ( 2 S ) traffic filter for real-time applications and b) the R2 - FLC (Reconfigurable Real-time Fuzzy Logic Controller) for on-line dynamic buffer size tuning. Inclusion of the 2 S filter into the extant RTPD (Real-time Traffic Detector) model creates the novel Enhanced RTPD (ERTPD) framework. The R2 - FLC uses the ERPTD to detect the current traffic pattern of a logical channel on the fly and auto-tunes accordingly. The auto-tuning process, which is system reconfiguration in the R2 - FLC context, neutralizes the ill effects by changing traffic patterns on the accuracy and stability of the dynamic buffer size tuning process.